PV system with maximum power point tracking: modeling, simulation and experimental results - Pereira, R. (2014)
This paper focuses on the five parameters modeling, consisting on a current controlled generator, single-diode, a shunt and series resistances. Also, a simulation, identification of the parameters for a photovoltaic system and the maximum power point tracking based on VP„g„g is presented. The identification of parameters and the performance of the equivalent circuit model for a solar module simulation are validated by data measured on the photovoltaic modules.